Impact of remote education on the mental health of university students during the pandemic of Covid-19 (Research, Society and Development, 2021)
Objective: Analyzing the scientific production on the impact of remote education on the mental health of university students during the Covid-19 pandemic. Method: This is a descriptive study of integrative review type of the literature. The search for articles was conducted through the Virtual Health Library (VHL), in the Databases Medical Literature Analysis and Retrieval System Online (MEDLINE), Nursing Database (BDENF), Latin American and Caribbean Literature on Health Sciences (LILACS) and Spanish Bibliographic Index in Health Sciences (IBECS), with the use of Descriptors in Health Sciences (DeCS): "coronavirus infections", "mental health" and "students", united with the Boolean operator "AND". Results: The searches in the databases rescued 145 articles, however after reading them, the final sample consisted of 6 articles that met the established eligibility criteria. Scientific evidence has shown the main damage of remote education to the mental health of university students in the face of the Covid-19 pandemic. There was emphasis on the symptoms of anxiety and depression. Conclusion: Given the current scenario, the students became a highly vulnerable public to the appearance of mental disorders, which enable the appearance of cognitive impairments, consequently affecting the development of learning.